Web-Based Management Information System Design for Student Organizations in Kendal Regency Using Next.js Framework - Fx Guntur Putra Susanto; Nizar Izzuddin Yatim Fadlan; Prita Haryani (Compiler, 2023)
Regional student organizations are essential for student development and fostering regional peer relationships. However, regional student organizations faced challenges in management due to the lack of digitization such as in the proposal’s approval, work programs submission, and accountability reports. With these challenges, the development of information systems was essential for simplifying regional student organization management and increasing member participation and involvement. This research focused on the information system design stage, which includes database design and interface design where the goal is to design an information system for student organizations in Kendal area using Node.js technology and Next.js frameworks that use the System Development Life Cycle with a waterfall model for the research method. Next.js is a popular framework that simplified web application development with server-side rendering and static site generation, enhancing system performance and reliability. In conclusion, the design of a Web-Based Management Information System for Student Organizations in Kendal Regency using the Next.js framework successfully incorporated various system components, including Unified Modelling Language diagrams, Entity-Relationship Diagrams, system architecture, and user interface design. The future research should focus on the development and implementation on the proposed system for further improvement of student organizations management in Kendal District.